2011
DOI: 10.1038/cddis.2011.105
|View full text |Cite
|
Sign up to set email alerts
|

Temporal blastemal cell gene expression analysis in the kidney reveals new Wnt and related signaling pathway genes to be essential for Wilms' tumor onset

Abstract: Wilms' tumors (WTs) originate from metanephric blastema cells that are unable to complete differentiation, resulting in triphasic tumors composed of epithelial, stromal and blastemal cells, with the latter harboring molecular characteristics similar to those of the earliest kidney development stages. Precise regulation of Wnt and related signaling pathways has been shown to be crucial for correct kidney differentiation. In this study, the gene expression profile of Wnt and related pathways was assessed in lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
0
21
1
1
Order By: Relevance
“…We and others have demonstrated that nephrogenesis and Wilms tumorigenesis share gene expression regulation patterns32333435. Furthermore, repression of miRNA maturation through inhibition of DROSHA and DICER1 expression impairs accurate kidney differentiation363738 and promotes tumorigenesis in several cell lines39.…”
Section: Discussionmentioning
confidence: 98%
“…We and others have demonstrated that nephrogenesis and Wilms tumorigenesis share gene expression regulation patterns32333435. Furthermore, repression of miRNA maturation through inhibition of DROSHA and DICER1 expression impairs accurate kidney differentiation363738 and promotes tumorigenesis in several cell lines39.…”
Section: Discussionmentioning
confidence: 98%
“…Wilms tumor is often associated with mutations in 11p15.5 and LOI of the IGF2 locus is found in nearly 90 % of Wilms tumor patients [54]. Previously, expression analysis of Wilm's tumor patients vs normal kidney showed a strong increase in IGF2 mRNA and a corresponding decrease in TIMP3 [55].…”
Section: Discussionmentioning
confidence: 99%
“…Of additional interest, HDGF (hepatoma-derived growth factor) was also sequenced from the list of peptide signatures, the gene locus for which is located at 1q22–23, as is CRABP2 , a region that if a gain in copy number occurs in FH WT, both event-free and overall survival are reduced. (24, 25) Interestingly, CRABP2 and HDGF have been previously shown to be upregulated at the mRNA level in WT blastema relative to embryonic kidneys.…”
Section: Resultsmentioning
confidence: 98%